(untitled) (Medico Legal Update, 2021)
Japan as a developed country needs a lot of productive labor to fulfill its human resources needs. With the revised Immigration Act of 2018, Japan has opened up to accept many migrant workers, one of whom is Indonesian migrant worker who can fulfill these needs. The purpose of this research is to find out the form of visa regulation for Indonesian migrant workers in Japan based on the provisions of the Japan Immigration Act 2018 and to know the efforts of the Indonesian Government can make in implementing the visa regulations to facilitate Indonesian migrant workers who will work in Japan.